2013
DOI: 10.3390/f4020433
|View full text |Cite
|
Sign up to set email alerts
|

Afforestation of Boreal Open Woodlands: Early Performance and Ecophysiology of Planted Black Spruce Seedlings

Abstract: Abstract:Open lichen woodlands (LWs) are degraded stands that lack the ability to regenerate naturally due to a succession of natural and/or anthropogenic disturbances. As they represent both interesting forest restoration and carbon sequestration opportunities, we tested disc scarification and planting of two sizes of containerized black spruce (Picea mariana Mill. (BSP)) seedlings for their afforestation. We compared treatment of unproductive LWs to reforestation of harvested, closed-crown black spruce-feath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…action potential to increase productivity. As a result, plans to afforest dry northern woodlands with jack pine, known for its generally more rapid growth and higher resilience to fire compared with black spruce, may need to be considered with caution (Rapanoela et al 2015), even if preliminary studies have shown some early successes (Tremblay et al 2013;Hébert et al 2014;Côté et al 2014).…”
Section: Findings and Implicationsmentioning
confidence: 99%
“…action potential to increase productivity. As a result, plans to afforest dry northern woodlands with jack pine, known for its generally more rapid growth and higher resilience to fire compared with black spruce, may need to be considered with caution (Rapanoela et al 2015), even if preliminary studies have shown some early successes (Tremblay et al 2013;Hébert et al 2014;Côté et al 2014).…”
Section: Findings and Implicationsmentioning
confidence: 99%
“…Bigger seedlings have a less branched root system and lower proportions of unsuberized fine roots, and could be less efficient in water and nutrient uptake (Johansson et al 2012). This different permeability of roots could also explain the higher concentration of several foliar nutrients observed in C25 compared to C50 (Tremblay et al 2013). The higher metabolism and greater capacity for enhancing photosynthesis should allow smaller and younger plants to endure the stress (Boege 2005).…”
Section: Size Vs Age Effectmentioning
confidence: 99%
“…Mansuy et al 2012). According to some authors, scarification may be used to favour tree regeneration, reduce conifer growth check by ericaceous species and ensure the return of productive closed-crown forest stands (Thiffault et al 2004(Thiffault et al , 2012Thiffault and Jobidon 2006;Veilleux-Nolin and Payette 2012;Tremblay et al 2013). Afforestation trials may help resolve these issues in a straightforward way.…”
Section: Discussionmentioning
confidence: 99%
“…However, as many of these sites were previously occupied by closed-crown forests (Simard and Payette 2005, Girard et al 2008, Mansuy et al 2012, it is now important to know if these sites, resulting from the natural conversion of closed-crown black spruce forests to open lichen woodlands, have maintained the potential to sustain adequate tree growth. This knowledge is key to understanding if reforestation of these sites could be a viable strategy for combating natural deforestation (Hébert et al 2006, Gaboury et al 2009, Mansuy et al 2012, Tremblay et al 2013. Considerations other than timber yield should also be taken into account, e.g., the importance of maintaining the continuous spruce feathermoss forests, which are concentrated in the eastern part of Canada, for their biodiversity and socioeconomic values (Gagnon and Morin 2001, Burton et al 2003, Gaboury et al 2009).…”
Section: Introductionmentioning
confidence: 99%